2021
DOI: 10.1002/bit.27890
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐cell‐density heterotrophic cultivation of the unicellular green alga Chlorella sorokiniana for biomass production

Abstract: Heterotrophic cultivation of Chlorella has achieved commercial success, but the application of Chlorella biomass is still limited due to the high cost of biomass production. In this study, an effective and industrially scalable heterotrphic cultivation technology has been developed for a production strain Chlorella sorokiniana GT‐1. Under the optimized culturing conditions, the ultrahigh biomass concentration of 271 and 247 g L−1 was achieved in 7.5 L bench‐scale and 1000 L pilot‐scale fermenters, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Heterotrophic culture offers the possibility to achieve high biomass concentration and stable scale-up cultivation of microalgae in well-controlled fermentor is readily achieved. Under 1,000-L pilot scale-up cultivation, the obtained maximum biomass concentrations of both Scenedesmus acuminatus and Chlorella sorokiniana were very close to those achieved in 7.5-L bench-scale fermentor cultivation (Jin et al, 2020;Jin et al, 2021). However, to date, only limited studies have been reported on fucoxanthin production through heterotrophic cultivation.…”
Section: Comparison Of Fucoxanthin Production By P Malhamensis With O...supporting
confidence: 60%
See 1 more Smart Citation
“…Heterotrophic culture offers the possibility to achieve high biomass concentration and stable scale-up cultivation of microalgae in well-controlled fermentor is readily achieved. Under 1,000-L pilot scale-up cultivation, the obtained maximum biomass concentrations of both Scenedesmus acuminatus and Chlorella sorokiniana were very close to those achieved in 7.5-L bench-scale fermentor cultivation (Jin et al, 2020;Jin et al, 2021). However, to date, only limited studies have been reported on fucoxanthin production through heterotrophic cultivation.…”
Section: Comparison Of Fucoxanthin Production By P Malhamensis With O...supporting
confidence: 60%
“…Biomass concentration was determined with GF/C filter paper as described in our previous report (Jin et al, 2021). Briefly, 1 ml of the culture was collected to centrifuge at 4,000 rpm for 3 min.…”
Section: Determination Of Biomass Concentration Cell Number and Gluco...mentioning
confidence: 99%
“…Usually, to achieve the fast growth, the optimal C/N ratio was kept for both initial batch medium and concentrated feeding medium ( Jin et al, 2020 ). Meanwhile, to maintain the C/N ratio constant, sodium hydroxide (NaOH) and potassium hydroxide (KOH) are two common alkali used for pH adjustment ( Xiong et al, 2008 ; Jin et al, 2021 ; Ma et al, 2021 ). Obviously, exogenous ions (Na + or K + ) would be introduced to the medium during this pH adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the biotechnical significance of heterotrophic cultivation for microalgal biomass and chemicals production ( Lee Chang et al, 2015 ; Morales-Sánchez et al, 2015 ; Hu et al, 2018 ). Through optimizing the components of growth media and substrate feeding strategy, ultra-high biomass yield (>200 g L −1 ) can be achieved for several production strains such as Chlorella sorokiniana ( Jin et al, 2021 ), Chlorella sorokiniana strain CMBB276 ( Xu et al, 2021 ) and Scenedesmus acuminatus ( Jin et al, 2020 ). The capabilities of these species in achieving such high biomass yield have been attributable to the highly active starch biosynthesis under heterotrophic conditions, considering the carbon substrate (i.e.…”
Section: Introductionmentioning
confidence: 99%